Efektivitas Pelayanan Program Kartu Identitas Anak Di Dinas Kependudukan Dan Pencatatan Sipil Kota Palu - Rustam, Anisa Amalia; Rivai, Abdul; Mukarramah (JPS: Journal of Publicness Studies, 2025)
Effectiveness of the Child Identity Card Program Services at the Population and Civil Registration Office of Palu City. This research aims to determine the effectiveness of the child identity card program services at the Population and Civil Registration Office of Palu City. The basis of this research uses qualitative research with a descriptive type. Data collection techniques were conducted through observation, interviews, and documentation. The data used in this study is based on the theory of effectiveness by Richard M. Steers (1985), which includes three indicators: goal achievement, integration, and adaptation. The results of this study indicate that in the goal achievement indicator, the annual target has been reached at 60%, the services provided are quite good, and the procedures are easy to understand. However, there are still delays in issuance caused by inadequate facilities and infrastructure, as well as from the community providing incomplete required documents, which slows down the service and delays the issuance. In the integration indicator, it was found that communication among employees has been established quite well. However, the socialization to introduce this program to the community has not been widespread. In the adaptation indicator, it is assessed as quite good due to adequate facilities and infrastructure and well-organized service rooms. However, the network sometimes experiences disruptions during service, and the availability of printer ink and paper is not always sufficient for reprinting forms, which hinders the smoothness of services and the issuance of child identity cards at the Population and Civil Registration Office of Palu City